I need to write the rules of inference and explain which rules of inference are used for each step. This looks like it's just Modus Ponens from what I wrote the equations as, am I missing some steps or is this really that simple?
“There is someone in this class who has been to France. Everyone who goes to France visits the Louvre. Therefore, someone in this class has visited the Louvre.”
C(x) “x is in this class”, F(x) “x has been to France”, L(x) “x visited the Louvre”
∃x(C(x) ∧ F(x))
∃x(C(x) ∧ L(x))